2007
DOI: 10.1007/s10549-007-9529-4
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter phase II trial of neoadjuvant exemestane for postmenopausal patients with hormone receptor-positive, operable breast cancer: Saitama Breast Cancer Clinical Study Group (SBCCSG-03)

Abstract: This multicenter phase II trial evaluated the efficacy and tolerability of 4 months of neoadjuvant exemestane in 44 postmenopausal patients with estrogen receptor (ER)-positive and/or progesterone receptor-positive, stage II to IIIB breast cancer measuring >or=3 cm. Pathological response was assessed by a central review board using response criteria proposed by the Japanese Breast Cancer Society. Clinical response [complete or partial response (PR)] was assessed by caliper, mammography, or ultrasound. Rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Several clinical studies have been reported using exemestane as primary endocrine therapy in operable breast cancer patients but results of clinical and pathological responses to exemestane varied among these studies [31][32][33][34]. Alterations in tumor histopathological features following aromatase inhibitors administration include the changes in cellularity, degree of fibrosis, histological grading [17,27], and treatment-related changes of cell proliferation, apoptosis, and hormone receptor expression were also described [31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have been reported using exemestane as primary endocrine therapy in operable breast cancer patients but results of clinical and pathological responses to exemestane varied among these studies [31][32][33][34]. Alterations in tumor histopathological features following aromatase inhibitors administration include the changes in cellularity, degree of fibrosis, histological grading [17,27], and treatment-related changes of cell proliferation, apoptosis, and hormone receptor expression were also described [31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical trials have shown that neoadjuvant endocrine therapy can contribute to down-staging and to improved therapeutic efficacy in HR-positive breast cancers [3][4][5]. Therefore, early identification of patients who do or do not respond to endocrine therapy is essential, allowing patients with less endocrinesensitive tumors to receive alternative treatments such as surgery or chemotherapy [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several trials have assessed the efficacy and safety of neoadjuvant endocrine therapy using aromatase inhibitors in patients with postmenopausal breast cancer [20][21][22][23][24][25]. In a randomized phase II study in which neoadjuvant endocrine therapy and neoadjuvant chemotherapy were compared in patients with hormone receptor-positive breast cancer, no significant difference in the clinical response rate was observed between the two groups [26].…”
Section: Neoadjuvant Endocrine Therapymentioning
confidence: 99%